International Trade, Noise Pollution, and Killer Whales - Taylor, Michael Scott,Mayer, Fruzsina (National Bureau of Economic Research, 2023)
Orcinus Orca is the world's largest predator, and simultaneously a significant tourist asset and cultural icon for much of the Pacific Northwest. In the past two decades, the Southern Resident Killer whale (SRKW) population has declined by more than 25 percent, putting them at risk of extinction. The cause of this decline is hotly debated. This paper employs novel data, an innovative noise pollution model, and quasi-experimental methods borrowed from environmental economics to solve this puzzle. We find consistent evidence that vessel noise pollution from international shipping has lowered fertility and raised the mortality of the SRKW significantly. Had noise pollution remained at its pre-1998 levels, the SRKW population would be 30% larger. Noise pollution is a growing threat to marine mammals worldwide
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Seefische; Artenschutz; Umweltbelastung; Lärm; Gewässerbelastung; Umweltökonomik; Trade; Sustainable Development; General; Air Pollution; Water Pollution; Noise; Hazardous Waste; Solid Waste; Recycling